Mekanisme Penggantian Antar Waktu (Paw) Anggota Dpr dan Implikasinya Dalam Konsep Perwakilan Rakyat - Rida Farida (Jurnal Cita Hukum, 2013)
Mechanism alteration of a ruling Member of Parliament (MP) and Its Implication to People Representation Concept. Alteration of a ruling Member of Parliament functioned as mechanism of control to political party that has representative in Parliament.  This regulation is obviously regulated in accordance with Act No 27 Year 2009 relating to People Representative Assembly, House of Representative and House of Regional Representative and Local House of Representative.  Nowadays, alteration of ruling MP becomes an effective mean to get rid of the MP whose ideas and visions are different with the political party where they belong. On the other hand, the existence of Member of Parliament is because of the election. DOI: 10.15408/jch.v1i2.2991